The Present Status of Screen Translation in China - Qian, Shaochang (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractIn a personal style, the author gives an overview of the recent past and the present status of screen translation in Mainland China. The audiovisual landscape has changed quickly, especially since 1978. The quality of dubbing is now in a vicious circle.